OPTIMALISASI SARANA DAN PRASARANA PENDIDIKAN SESUAI STANDAR NASIONAL PENDIDIKAN DI SMPN 12 BANDUNG - Keisha Azahra Fauzita; Delisa Hafidah; Fitriyani Dwi Azzahra; Muhammad Hafizd Fauzi (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to analyze the compliance of educational facilities and infrastructure at SMPN 12 Bandung with the National Education Standards (SNP). The research employs a descriptive qualitative method, with data collected through observations, interviews, and document analysis. Primary data was obtained through face-to-face interviews with the Principal in charge of Facilities and Infrastructure, while secondary data included supporting documents. The analysis revealed that several facilities, such as the principal’s office (75%), classrooms (72.05%), and the sports field (34.47%), do not meet the SNP’s area standards, impacting comfort and the effectiveness of learning activities. However, other facilities, such as the counseling room (355.55%) and the prayer room (1,666.67%), exceed the minimum standards, offering potential for additional service development. These findings highlight the need for renovations, spatial optimization, and strategic planning to enhance the quality of the learning environment and address the needs of both students and teachers. This study provides insights into the challenges and opportunities in managing school facilities and infrastructure, emphasizing the importance of adhering to educational standards to create an optimal learning environment.